How Do Violent Politicians Govern? The Case of Paramilitary-Tied Mayors in Colombia. Issue 4 (6th October 2022) - Daly, Sarah Zukerman
Abstract: How do politicians with coercive linkages govern? This article relies on original data on militia-linked mayors in Colombia from 1988 to 2015 derived from 42, 000 pages of Colombian Supreme Court sentencing documents. Using a regression discontinuity design, it examines the governance records of militia-tied mayors who won the elections by a narrow margin. It finds that being ruled by a militia-linked mayor significantly reduces levels of insecurity and crime, but has pernicious effects on the provision of other public goods, especially education. I theorize that these politicians' (perverse) comparative advantage on security, combined with their crowding out of social spending, engenders these outcomes. I evaluate these mechanisms with data on the nature of paramilitary–mayor alliances, police reinforcements, municipal budgets, politicians' Twitter feeds, and in-depth interviews with paramilitary commanders and politicians. The article has implications for understanding the effects of voting for politicians with coercive ties on the quality of governance and democracy.